Determinação de parâmetros cinéticos e dimensionamento de um reator batelada para extração de astaxantina de resíduos do camarão branco do pacífico (L. vannamei) - Brandão, Lucas Barbosa (2020)
During the process of processing the shrimp, the waste generated has several molecules with great economic potential when recovered, among them, we have astaxanthin. Astaxanthin is a natural red pigment widely used in aquaculture as an additive in the diet of salmonids (salmon and trout). The commercial market is dominated by synthetic astaxanthin and the use of organic solvents. However, in recent years, alternatives have been sought to make the production of natural astaxanthin possible, becoming an option and a substitute for synthetic astaxanthin. Extraction of astaxanthin with vegetable oils/vegetable oil ester is one such method. The method takes advantage of the liposolubility of astaxanthin to obtain the molecule. The objective of the present work was to design a batch reactor to extract astaxanthin from the Pacific white (Litopenaeus vannamei) residues. For this, bench scale experiments were carried out to evaluate the influence of temperature, solvent/residue ratio and agitation on the extraction yield and to determine the optimal solvent and optimal conditions for obtaining astaxanthin. The best results found were 128.47 µg/g for soy oil extraction and 107.16 µg/g for soy oil methyl ester extraction. At low temperatures (30º and 60ºC), the methyl ester showed better extraction yield than in soybean oil due to its low viscosity. At high temperatures (90ºC), the yield of the two extractions was similar. However, the cost of obtaining the ester made the oil a better alternative as an extraction solvent. The extraction was well represented by a first order kinetic model with degradation. The values for the specific reaction speeds, k1 and k2, of 3.2 x 10-2 min-1 and 1.58 x 10-2 min-1 and served as a basis for the design of a batch reactor for extraction of astaxanthin predicting a 50g of astaxanthin/day. The volume of the reactor required for the process was 1.5 m³, considering a safety margin of 30%. The ratio of the geometric parameters of the bench reactor /reactor was 10x higher. The sizing of the reactor is a great way to combine the recovery of molecules with great commercial value and application with the reduction of the discharge of pollutants in the environment.